Complex Case: Acute-on-Chronic Gouty Arthritis, Septic Arthritis, and Severe Joint Deformities in a Young Adult Patient - Dwi Putri Anjani, I Gusti Agung; I Made Bayu Indratama; Prisca Oriana Sutanto (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Gout is the most prevalent type of inflammatory arthritis, which can lead to inflammation in the joints. However, septic arthritis is unusual in gout. Case presentation: A 34-year-old male presented with lumps on the right ankle with cloudy white fluid discharge for 5 days prior to admission. The patient also has lumps observed on the left pedis, and manus bilateral. The patient regularly takes Allopurinol daily and Piroxicam prior to admission. The physical examination had a limited range of movement. Laboratory examinations found elevated uric acid, impaired renal function, elevated white blood cells, and elevated erythrocyte sedimentation rate. The patient was then referred for surgical debridement. Conclusion: Chronic gout marked by persistent polyarticular engagement and the formation of tophi. In individuals left untreated, septic arthritis and gout may manifest, followed by deformities of joints, which need further diagnosis and management.